Outcomes after fractional flow reserve-guided percutaneous coronary intervention versus coronary artery bypass grafting (FAME 3): 5-year follow-up of a multicentre, open-label, randomised trial - Fearon, William F; Zimmermann, Frederik M; Ding, Victoria Y; Takahashi, Kuniaki; Piroth, Zsolt; van Straten, Albert H M; Szekely, Laszlo; Davidavičius, Giedrius; Kalinauskas, Gintaras; Mansour, Samer; Kharbanda, Rajesh; Östlund-Papadogeorgos, Nikolaos; et al. (Lancet, 2025)
BACKGROUND: Long-term outcomes following percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) might be changing because of improved techniques and better medical therapy. This final prespecified analysis of the Fractional Flow Reserve (FFR) versus Angiography for Multivessel Evaluation (FAME) 3 trial aimed to reassess their comparative effectiveness at 5 years. METHODS: FAME 3 was a multicentre, randomised trial comparing FFR-guided PCI using current-generation zotarolimus-eluting stents versus CABG in patients with three-vessel coronary artery disease not involving the left main coronary artery. 48 hospitals in Europe, USA and Canada, Australia, and Asia participated in the trial. Patients (aged ≥21 years with no cardiogenic shock, no recent ST segment elevation myocardial infarction, no severe left ventricular dysfunction, and no previous CABG) were randomly assigned to either PCI or CABG using a web-based system. At 1 year, FFR-guided PCI did not meet the prespecified threshold for non-inferiority for the outcome of death, stroke, myocardial infarction, or repeat revascularisation versus CABG. The primary endpoint for this intention-to-treat analysis was the 5-year incidence of the prespecified composite outcome of death, stroke, or myocardial infarction. The trial was registered at ClinicalTrials.gov, NCT02100722, and is completed; this is the final report. FINDINGS: Between Aug 25, 2014 and Nov 28, 2019, 757 of 1500 participants were assigned to PCI and 743 to CABG. 5-year follow-up was achieved in 724 (96%) patients assigned to PCI and 696 (94%) assigned to CABG. At 5 years, there was no significant difference in the composite of death, stroke, or myocardial infarction between the two groups, with 119 (16%) events in the PCI group and 101 (14%) in the CABG group (hazard ratio 1·16 [95% CI 0·89-1·52]; p=0·27). There were no differences in the rates of death (53 [7%] vs 51 [7%]; 0·99 [0·67-1·46]) or stroke (14 [2%] vs 21 [3%], 0·65 [0·33-1·28]), but myocardial infarction was higher in the PCI group than in the CABG group (60 [8%] vs 38 [5%], 1·57 [1·04-2·36]), as was repeat revascularisation (112 [16%] vs 55 [8%], 2·02 [1·46-2·79]). INTERPRETATION: At the 5-year follow-up, there was no significant difference in a composite outcome of death, stroke, or myocardial infarction after FFR-guided PCI versus CABG, although myocardial infarction and repeat revascularisation were higher with PCI. These results provide contemporary evidence to allow improved shared decision making between physicians and patients. FUNDING: Medtronic and Abbott Vascular.
Keywords: Coronary Angiography; Humans; následné studie; lidé středního věku; Middle Aged; Percutaneous Coronary Intervention; nemoci koronárních tepen; Drug-Eluting Stents; Follow-Up Studies; Coronary Artery Disease; mužské pohlaví; frakční průtoková rezerva myokardu; sirolimus; stenty uvolňující léky; Sirolimus; výsledek terapie; Fractional Flow Reserve, Myocardial; koronární bypass; Coronary Artery Bypass; Myocardial Infarction; Treatment Outcome; koronární angioplastika; ženské pohlaví; infarkt myokardu; lidé; Aged; senioři; Male; koronární angiografie; Female